DIPG-27. OPTIMIZING CLINICAL TRIAL DESIGN: PHARMACOKINETICS OF MARIZOMIB AND PANOBINOSTAT IN A NON-HUMAN PRIMATE MODEL. (23rd April 2019) - Warren, Katherine; Shankarappa, Priya; Peer, Cody; Garcia, Rafael Cruz; Monje-Deisseroth, Michelle; Figg, W Doug; McCully, Cynthia Lester
Abstract: BACKGROUND: Pre-clinical determination of disease-specific activity, effective dosing, safety, pharmacokinetics, and CNS delivery can optimize clinical trial designs. The proteasome inhibitor, marizomib, together with the HDAC inhibitor, panobinostat, is active and synergistic in pre-clinical DIPG studies, with target concentrations of 20 and 100 nM, respectively. The adult maximum tolerated dose (MTD) for marizomib is 0.8 mg/m 2 . We evaluated the safety, tolerability and pharmacokinetics in a non-human primate model, predictive of pediatric patients. METHODS: Marizomib was administered (10-minute intravenous infusion) at three dose levels: 0.02 (n=4), 0.04 (n=5), and 0.06 mg/kg (n=1), equivalent to human doses (HED) of 0.4, 0.8, and 1.1 mg/m 2, respectively. Marizomib (dose 0.04 mg/kg) was subsequently administered (n=4) 1-hr post-panobinostat (dose 1 mg/kg, HED 20 mg/m 2, p.o.). Drug concentrations were determined by LC-MS/MS using validated assays and PK parameters calculated via noncompartmental methods. RESULTS: Marizomib +/- panobinostat was tolerable with the exception of one animal (single agent marizomib, dose 0.06 mg/kg, HED= 1.2 mg/m 2 ) that expired 12–20 hr post administration; no clear etiology was found at necropsy. Remaining adverse events were Gr 1, 2 with the exception of lymphocytopenia, Gr 3 (n=2). Marizomib demonstrated rapid plasma clearance (1.22–10.25 L/min), short plasma half-life (4.45–8.24 min), non-linear increase in AUCinf, and no significant difference across dose levels. Conversely, in CSF, there was a trend toward increasing exposure with increasing dose. T1/2 was longer in CSF than blood (18–25 min vs. 4–7 min, respectively). Comparing marizomib PK before and after panobinostat, t1/2 and clearance were similar (mean 7.80 vs. 9.49 min, and 6.04 vs. 4.24 L/min, respectively); CSF AUCinf increased, 65.69 vs. 121.68 min*nM, respectively. CONCLUSIONS: Marizomib penetrates into the CNS and CSF exposure was higher after panobinostat. This combination warrants clinical evaluation in DIPG; correlation of results with preclinical findings is planned.